New alternatives in veterinary anthelminthic therapy - Romeo T. Cristina (Medicamentul Veterinar)
Present paper proposes the presentation of antiparasitic boluses, veterinary use specific conditionings with importance in gastro intestinal helminth population control, as a modern alternative to the classic antihelmintic therapy. The active substances are released consecutive to: diffusion, osmotic procesess, to progressive erosion, or through electronic programmed devices. Anthelmintic boluses are classified upon the releasing system in: a) anthelmintic sustained release systems: for albendazole (Proftril bolus), morantel tartrate (Paratect flex and bolus) ivermectines (Enzec and Alzet, Ivomec SR Bolus), levamisole (Chronominthic bolus), oxfendazol (Synanthic multidose bolus) fenbendazole (Panacur Bolus).b) anthelmintic programmed periodic release systems: Intra Ruminal Pulse Release Electronic Device (I.R.P.R.E.D) and Repidose (Autoworm, Oxfendazole Pulsed Release Bolus).